BY DEDE NIYAZI ARSLAN ON THE ADİYAMAN ALEVISM - Fevzi RENÇBER (Fırat University, 2019)
In the present days unsuitable comments on Alevism are expressed, that causes misunderstanding the Anatolian Alevism, especially exclusive of its traditional line. Our study, that effort to understanding traditional Alevism, based on interview with “Lover of God and Bard” Dede Niyazi Arslan. Dede Niyazi Arslan is serving to Alevism candidates in Adıyaman provinces Gölbaşı and Besni. Also he struggled through his life to live and keep alive Alevism faith between rising generations. This study was prepared compiling the answers to the questions we asked such as; what is Alevism; the place of whirl in Alevi understanding; Deity-Mohammed-Ali belief in Alevism; What does the statement "Performed Ablution, Performed Ritual Worship"; mean afterlife belief in Alevism; place of woman in Alevism; local practices of "Dardan İndirme Erkanı" performed for the Alevism who died; the contents of "dört kapı-kırk makam" that forms the basis of Alevism way; what is promising in Alevi belief and what are the features of "Alevi talip"; how do “cem evi” operate today and what are the problems of “cem evi”; what are the problems of Alevi society and what are their requests from the government; importance of cem sacrifice and aşura sacrifice in Muharrem month; place and importance of "Mohammed Postu" in "cem erkân"; importance of fasting in Muharrem in Alevism; twelve imams in Alevism; and the questions asked to the importance of Hz. Ali and Hz. Hüseyin. Fieldwork is essential in the Alevism studies. Therefore, this study we conducted in the region of Adiyaman serves an important purpose such as understanding traditional Anatolian Alevism.